Combustion Turbulence Flow in the Advanced Vortex Combustor with Built-In Obstacles - Yu Chen; Zhuoxiong Zeng; Haoyuan Wang (International Journal of Aerospace Engineering)
To obtain the advanced vortex combustor (AVC) and its optimal structure parameters in light of built-in obstacles, numerical simulation was performed. This research shows that inclined struts have optimal structural parameters with inclination angle α=30° and blocking ratio BR=12%, while guide vane and its optimal structural parameter have three layers, which are a/B=0.1, b/h=0.4, and c/L=0.2, respectively; blunt body has the biggest height of H1/B1=2/3. According to these statistics, the research studies how inlet factors affect turbulence flow in combustion. The research finds increases in inlet velocity and flow resistance are in positive correlation. As inlet temperature increases, the flow resistance decreases. From field synergy theory, inlet factor has different effect on the heat transfer performance.